Creative Thinking in Solving Non-Routine Mathematical Problems Through the Creative Problem Solving-Treffinger Model - Hasan, Buaddin; Jamil, Anis Farida; Wicaksono, Arief Budi (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2026)
This study analyzes students’ creative thinking processes in solving non-routine mathematical problems using Treffinger’s Creative Problem Solving (CPS) stages. The subjects included students with high, medium, and low mathematical abilities. Data were collected through worksheet analysis, visual representations, mathematical work, and semi-structured interviews, then analyzed using data condensation, display, and conclusion drawing. Researchers use time triangulation to validate the data. The findings show that creative thinking develops in stages and differs by ability level. High-ability students complete all CPS stages optimally, demonstrating deep understanding, flexible and original strategies, and reflective evaluation, with all creativity indicators (fluency, flexibility, originality, and elaboration) consistently emerging. Medium-ability students show a developing but unstable process; they can understand problems and generate ideas, but remain limited in strategy variation and evaluation. Low-ability students exhibit procedural thinking, marked by misconceptions, incomplete representations, minimal idea exploration, and a lack of evaluation. Overall, the CPS-Treffinger model is effective in fostering creative thinking but requires adaptation to students’ ability levels. Teachers should design non-routine problem-based learning that encourages idea exploration, multiple representations, and reflective thinking to support the development of mathematical creativity.